From Amoraic Authority to Stammaitic Dialectics: Difficulties Based on Amoraic Sources in the Babylonian Talmud - Cohen, Barak S. (Jewish studies quarterly, 2025)
When considering issues of rabbinic legal authority, hierarchy and other subjects related to rabbinic interactions, the difficulty arises of how to explain the hundreds of instances in which the Babylonian Talmud uses the words of one amoraic sage to challenge another. This study reevaluates the explanations of this phenomenon suggested in modern scholarship and offers my own findings. I analyze three types of difficulties raised from amoraic sources found in the Bavli, including: (1) "But did R. X not say …?"; (2) "Does the master not agree with what R. X said …?" and (3) "Was it not stated about this …?!/Behold it was stated about this …." The results of this analysis lead to a new way of understanding the development of talmudic dialectics (from amoraic to stammaitic) and the dating of the stam in the Bavli. In light of these findings, it will also be possible to understand how certain trends in legal rulings were formed and developed in talmudic Babylonia.